2013
DOI: 10.1038/cddis.2013.150
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase 1B modulates GSK3β/Nrf2 and IGFIR signaling pathways in acetaminophen-induced hepatotoxicity

Abstract: Acute hepatic failure secondary to acetaminophen (APAP) poisoning is associated with high mortality. Protein tyrosine phosphatase 1B (PTP1B) is a negative regulator of tyrosine kinase growth factor signaling. In the liver, this pathway confers protection against injury. However, the involvement of PTP1B in the intracellular networks activated by APAP is unknown. We have assessed PTP1B expression in APAP-induced liver failure in humans and its role in the molecular mechanisms that regulate the balance between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 48 publications
7
69
0
Order By: Relevance
“…However, 10 × 10 −3 m APAP exposure significantly decreased the cell viability after day 7. These results correlated well with results obtained from the literature and our previously published study 42. Remarkably, our data showed that the trend in cell viability at each day was consistent with the variation of albumin and GST‐α production rates at the same time points.…”
Section: Resultssupporting
confidence: 92%
“…However, 10 × 10 −3 m APAP exposure significantly decreased the cell viability after day 7. These results correlated well with results obtained from the literature and our previously published study 42. Remarkably, our data showed that the trend in cell viability at each day was consistent with the variation of albumin and GST‐α production rates at the same time points.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, there is growing evidence to suggest that the dysregulation of protein kinase phosphatases may influence APAP toxicity (Wancket et al, 2012). Protein tyrosine phosphatase 1B null mice are more resistant to APAP than wild-type mice and have reduced levels of phosphorylated JNK in response to APAP (Mobasher et al, 2013). Interestingly, previous reports have demonstrated that protein tyrosine phosphatase 1B S-glutathionylation results in enzyme inactivation (Barrett et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…CK2 interacts with two phosphorylated forms of Nrf2, specifically Nrf2-118 and Nrf2-98, the latter of which has transcription activity, which makes it easier for it to degrade (Pi et al 2007). Additionally, glycogen synthesis kinase 3 (GSK3; Chowdhry et al 2013, Mobasher et al 2013) and RNA-dependent protein kinase endoplasmic reticulum enzyme also phosphorylate Nrf2 (Zhang et al 2014b).…”
Section: Regulation Of the Nrf2-are Pathwaymentioning
confidence: 99%